SCANNING ELECTRON MICROSCOPIC STUDIES ON THE CUTICULAR STRUCTURES OF THE PUPA OF DROSOPHILA ANANASSAE - CHAKRABARTI, C.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Drosophila ananassae like many other insects complete their life-cycle through egg-larva-pupa and adult. Pupal stage exists for about 5-6 days, depending upon some factors. This non-motile form develops from the most active andmotile third instar larval stage. Drastic changes have been noticed during the metamorphosis of a larva to a pupa. Many of these changes areassociated with the cuticle of the pupa. Present studies have revealed that most of the cuticular structure found in a third instar larvae undergo degeneration alongwith the metamorphosis of a larvae into a pupa.